2018
DOI: 10.1111/epi.14606
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition in childhood epilepsy: Impact on mortality and complete seizure remission 50 years later

Abstract: Objective:To study associations of the severity of impairment in childhood neurocognition (NC) with long-term mortality and complete seizure remission. Methods: A population-based cohort of 245 subjects with childhood onset epilepsy was followed up for 50 years (median = 45, range = 2-50). Childhood NC before age 18 years was assessed as a combination of formal intelligence quotient scores and functional criteria (school achievement, working history, and psychoneurological development). Impaired NC was categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…Most children who died had severe or profound ID, as previously reported. 33 Our estimate of mortality before 16 years of age of 13% for DEE was lower than the 21% previously reported. 22 This difference may relate to the previous study having a longer observed period (up to 20 years, median follow-up of 16 years) and their result being an absolute number of deaths in their cohort (12/58, 21%) rather than an estimate of mortality at a set age.…”
Section: Discussioncontrasting
confidence: 74%
“…Most children who died had severe or profound ID, as previously reported. 33 Our estimate of mortality before 16 years of age of 13% for DEE was lower than the 21% previously reported. 22 This difference may relate to the previous study having a longer observed period (up to 20 years, median follow-up of 16 years) and their result being an absolute number of deaths in their cohort (12/58, 21%) rather than an estimate of mortality at a set age.…”
Section: Discussioncontrasting
confidence: 74%
“…As listed in Figure 4 , the demographics, disease characteristics (such as early age of epilepsy onset and duration of epilepsy), underlying neuropathologies, as well as static and dynamic variables with potential for cognitive impairment, should be evaluated. 55 , 56 While some factors (eg, location and severity of underlying lesions) are static and cause chronic impairments; other factors (eg, seizure frequency and severity) are dynamic and potentially reversible, and may be manageable with clinical intervention. 53 , 56 , 57 …”
Section: Cognitive Dysfunction In Epilepsymentioning
confidence: 99%
“…Prolonged bed rest and immobility as widely known problems of children with severe cerebral palsy can greatly weaken their immunity and increase risks of severe illness and hospitalization. Hence, those who have neurological impairment leading to bed ridden state have a likelihood of a developing severe illness or other complications [29]. On the contrary, Balestrini et al have reported that even adult patients with epilepsy and multiple comorbidities show a high percentage of asymptomatic conditions, indicating that comorbidities factors do not necessarily lead to poor outcomes [30].…”
Section: A B C Time From Diagnosi Viruses Comorbiditimentioning
confidence: 99%